Preoperative prediction for early recurrence can be as accurate as postoperative assessment in single hepatocellular carcinoma patients - Cha, Dong Ik; Jang, Kyung Mi; Kim, Seong Hyun; Kim, Young Kon; Kim, Honsoul; Ahn, Soo Hyun (Korean Journal of Radiology, 2020)
Objective: To evaluate the performance of predicting early recurrence using preoperative factors only in comparison with using both pre-/postoperative factors. Materials and Methods: We retrospectively reviewed 549 patients who had undergone curative resection for single hepatcellular carcinoma (HCC) within Milan criteria. Multivariable analysis was performed to identify pre-/postoperative high-risk factors of early recurrence after hepatic resection for HCC. Two prediction models for early HCC recurrence determined by stepwise variable selection methods based on Akaike information criterion were built, either based on preoperative factors alone or both pre-/postoperative factors. Area under the curve (AUC) for each receiver operating characteristic curve of the two models was calculated, and the two curves were compared for non-inferiority testing. The predictive models of early HCC recurrence were internally validated by bootstrap resampling method. Results: Multivariable analysis on preoperative factors alone identified aspartate aminotransferase/platelet ratio index (OR, 1.632; 95% CI, 1.056–2.522; p = 0.027), tumor size (OR, 1.025; 95% CI, 0.002–1.049; p = 0.031), arterial rim enhancement of the tumor (OR, 2.350; 95% CI, 1.297–4.260; p = 0.005), and presence of nonhypervascular hepatobiliary hypointense nodules (OR, 1.983; 95% CI, 1.049–3.750; p = 0.035) on gadoxetic acid-enhanced magnetic resonance imaging as significant factors. After adding postoperative histopathologic factors, presence of microvascular invasion (OR, 1.868; 95% CI, 1.155– 3.022; p = 0.011) became an additional significant factor, while tumor size became insignificant (p = 0.119). Comparison of the AUCs of the two models showed that the prediction model built on preoperative factors alone was not inferior to that including both pre-/postoperative factors {AUC for preoperative factors only, 0.673 (95% confidence interval [CI], 0.623– 0.723) vs. AUC after adding postoperative factors, 0.691 (95% CI, 0.639–0.744); p = 0.0013}. Bootstrap resampling method showed that both the models were valid. Conclusion: Risk stratification solely based on preoperative imaging and laboratory factors was not inferior to that based on postoperative histopathologic risk factors in predicting early recurrence after curative resection in within Milan criteria single HCC patients.
Keywords: Adult; Aged; Aged, 80 and over; Area Under Curve; Aspartate Aminotransferases; Blood Platelets; Carcinoma, Hepatocellular; Female; Humans; Liver Neoplasms; Magnetic Resonance Imaging; Male; Middle Aged; Neoplasm Recurrence, Local; Odds Ratio; Preoperative Period; Prognosis; Retrospective Studies; Risk Factors; ROC Curve; Imaging factors; Laboratory factors; Pathologic factors; Prediction model